Interconnection of Life Insurance and State of Health of the Population in Ukraine - Arych, Mykhailo; Levon, Mariia (My University, 2018)
У науковому дослідженні проаналізовано сучасний стан взаємозв’язку системи страхування життя та стану якості здоров’я населення. Встановлено та обґрунтовано, що ринок страхування життя є важливим та обов’язковим елементом забезпечення високого рівня здоров’я та підвищення тривалості життя громадян країни. The scientific research analyzes the current state of the relationship between the life insurance system and the quality of health of the population. It is established and substantiated that the life insurance market is an important and obligatory element of ensuring a high level of health and improving the life expectancy of citizens of the country.
Keywords: страховий ринок; страхування життя; здоров’я населення; кафедра фінансів; insurance market; life insurance; public health